His Eminence Sheikh / Essam bin Hussein Bukhari | فضيلة الشيخ/عصام بن حسين بخاري (Al-Madinah Al-Munawwarah Research and Studies Center | مركز بحوث ودراسات المدينة المنورة, 2023)
- The school of readings in order to memorize the Qur’an in it, they used to give us 30 riyals a month (silver)